2010
DOI: 10.1016/j.virol.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of immune responses to Russian spring–summer encephalitis and Omsk hemorrhagic fever viruses in mouse models

Abstract: Omsk hemorrhagic fever virus (OHFV) and Russian spring-summer encephalitis virus (RSSEV) are tick-borne flaviviruses that have close homology but different pathology and disease outcomes. Previously, we reported that C57BL/6 and BALB/c mice were excellent models to study the pathology and clinical signs of human RSSEV and OHFV infection. In the study described here, we found that RSSEV infection induced robust release of proinflammatory cytokines (IL-1α, IL-1β, IL-6 and TNF-α) and chemokines (MCP-1, MIP-1β, RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
5
15
0
Order By: Relevance
“…We did not find significant amounts of virus in the brain or lungs, which also corresponds with what has been observed for OHFV [26]. Similar to what has been observed by others upon OHFV infection, AHFV induces a pro-inflammatory cytokine response early in the kidney and spleen, and differences in some hematologic parameters, namely leukopenia combined with decreases in lymphocytes, RBC count, hemoglobin levels, and hematocrit [28], indicating that AHFV Zaki-1 causes a sub-clinical hemorrhagic-like syndrome. Lethal infection of mice with TBEV is not associated with elevated body temperatures [40], while animals infected with KFDV in our study had transient fever during the later phase of disease.…”
Section: Discussionsupporting
confidence: 91%
“…We did not find significant amounts of virus in the brain or lungs, which also corresponds with what has been observed for OHFV [26]. Similar to what has been observed by others upon OHFV infection, AHFV induces a pro-inflammatory cytokine response early in the kidney and spleen, and differences in some hematologic parameters, namely leukopenia combined with decreases in lymphocytes, RBC count, hemoglobin levels, and hematocrit [28], indicating that AHFV Zaki-1 causes a sub-clinical hemorrhagic-like syndrome. Lethal infection of mice with TBEV is not associated with elevated body temperatures [40], while animals infected with KFDV in our study had transient fever during the later phase of disease.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to our study, the extent of BBB permeability was in direct association with increased levels of cytokines, clinical sickness, and virus titer in the brains of JEV-infected mice [27]. Robust release of some of the investigated cytokines/chemokines in the brains of TBEV-infected mice has also been recently demonstrated by other authors [28], [29]. It is known that the overproduction of proinflammatory cytokines, including TNF-α and IL-6, enhances neuronal injury [30] and increases BBB permeability [31], [32].…”
Section: Discussionsupporting
confidence: 87%
“…Thus, our findings demonstrate that a similar chemokine expres- sion pattern during viral encephalitis is evident regardless of the pathogen. Similar, but more limited, observations have been made for a number of viruses that cause encephalitis, including herpes simplex virus 1 (42), tick-borne encephalitis virus (43), and lyssaviruses (44). Based on our FACS data, we have demonstrated that mostly CD8 ϩ T cells and monocytes infiltrate the brain during SFV infection.…”
Section: Discussionsupporting
confidence: 84%